Efficient Onboarding and Management of Members in Permissioned Blockchain Networks Utilizing TLS Certificates - Gallersdörfer, Ulrich; Strugala , Jan-Niklas; Matthes, Florian (Frontiers in Blockchain, 2021)
Consortia blockchain networks face the issue of expanding their systems to new members. Onboarding processes are often cumbersome, as they require identifying the new participant, manually setting up rights, exchanging key material, and adding information about the new member to the consensus smart contract. Besides that, these processes are time-consuming and scale poorly. Identifying the members might be faulty as the pre-existing members might be deceived by malicious parties claiming to be someone else. This paper proposes a novel methodology to allow the onboarding of new parties without time-intensive off-chain processes. We establish identities of new consortia members by utilizing TLS certificates bound to publicly known domain names. With this identity scheme in place, the network operators can define rules such as only specific parties are allowed to join the network, e.g., only owners of *.edu domains. This methodology scales well, provides for extensive ruling and monitoring, and helps consortia blockchains to grow faster.